Oxidative stress and inflammation: the root causes of aging - Prasert Sobhon; Gavin Savedvanich; Sawaek Weerakiet (Open Exploration Publishing Inc., 2023)
Oxygen free radicals [reactive oxygen species (ROS)] and nitrogen free radicals [reactive nitrogen species (RNS)] are generated by mitochondria during adenosine triphosphate synthesis, and catalytic activities of cytochrome P450, nicotinamide adenine dinucleotide phosphate oxidases (NOXs), cyclooxygenases, and nitric oxide synthases during drug catabolism, phagocytosis, and acute inflammation. Under normal circumstances, low levels of ROS and RNS provide redox signalings that control many essential physiological processes. As age progresses ROS and RNS increase excessively due to dysfunctional mitochondria, dysregulated NOX, and other free-radical generating sources, leading to oxidative stress, which causes oxidation and denaturation of key cellular components including DNA, proteins, and lipids, which become abnormal, constituting damage-associated molecular pattern (DAMP), recognized as 'non-self' by immune cells, leading to inflammation which is mediated by nuclear factor kappa B-inflammasome, p38-c-Jun N-terminal kinase and Janus kinase-signal transducer and activator of transcription pathways. DAMPs are continuously released from damaged and senescent cells, causing an otherwise normally transient inflammation turning into systemic chronic inflammation, the root cause of aging and age-associated diseases (AADs). Cells restore redox balance by activating the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway that induces the synthesis and release of antioxidation molecules and enzymes including haem oxygenase-1, which also inhibits the three inflammatory pathways. Furthermore, upregulation of autophagy (AP) can get rid of abnormal molecules, prevent the generation of DAMPs, and attenuate inflammation. Both AP and Nrf2 signalings decrease with age. The upregulations of Nrf2, AP, and downregulation of inflammation are controlled by sensors of energy and stress levels, i.e., adenosine monophosphate-activated protein kinase, silent information regulator 1, and Sestrins, as well as the extracellular matrix, while mammalian targets for rapamycin complex 1, a nutrient sensor, act in the opposite direction. If the balance of these sensor systems becomes dysregulated, aging process accelerates, and the risk of AADs increases.